Crystallisation of ferrous sulphate heptahydrate: experiments and modelling - Shaikh, Latif; Pandit, Aniruddha; Ranade, Vivek (Canadian Journal of Chemical Engineering, 2013)
Crystallisation is an industrially important unit operation for purifying and separating chemical mixtures. A generic crystallisation modelling framework has been implemented in the general process modelling system (gPROMS) software (of PSE, UK). This framework can be used to model the batch cooling crystallisation of ferrous sulphate heptahydrate (FSH). The parameter estimation and sensitivity of the predicted results with various numerical parameters was studied for batch crystalliser. An Excel front-end to the gPROMS model was developed to facilitate the interactive use of the model. (c) 2011 Canadian Society for Chemical Engineering
Keywords: batch crystallisation; ferrous sulphate heptahydrate; gPROMS; MSExcel-linking; parameter estimation

Effect of turbulent dispersion on hydrodynamic characteristics in a liquid jet ejector - Sharma, Deepankar; Patwardhan, Ashwin; Ranade, Vivek (Energy, 2018)
Gas induction using a liquid jet is an extensively studied phenomenon. Many studies have been published detailing various hydrodynamic and mass transport aspects of gas induction in ejectors. Conversely, multiple studies have been published detailing jet dynamics, jet break up, nozzle geometry, effects of turbulence etc. In the modelling of the jet ejector systems CFD framework is used as the flow of gas is coupled with the liquid flow and the flow parameters like volume fraction, pressure drop/profile and velocity profiles both local and average are highly interdependent. Hence, it becomes important to capture all the flow physics in the simulations in order to understand the hydrodynamics. In the previous models the effect of turbulent dispersion was not included which led to incorrect calculation of phase profile, and other related parametric values. In the present work, the turbulence effects and its impact on the jet dynamics and gas induction rate in an ejector have been studied. Capturing the correct phase as well as velocity profile is imperative for the extension of the model to mass transfer and reactions. Lastly, other hydrodynamic properties like pressure drop, phase hold up and pressure profile help better the design correlations for jet ejectors.

Characterization of axial dispersion in a vertical helical coil for gas-liquid-liquid flow at low Reynolds numbers - Khan, Muzammil; Joshi, Sunil; Ranade, Vivek (Reaction Chemistry & Engineering, 2022)
Gas-liquid-liquid (GLL) slug flow reactors offer several advantages like higher interfacial area, excellent mass transfer, and lower backmixing. Mesoscale (diameter similar to a few mm) helical coiled reactors operating in a slug flow regime can be used as GLL reactors even for reactions with long residence times. The long residence time invariably leads to low Reynolds number flows, which makes the backmixing or axial dispersion an important parameter influencing reactor performance. In this work, we have characterized the residence time distribution (RTD) and axial dispersion for single, gas-liquid, liquid-liquid, and gas-liquid-liquid flows through a vertical helical coil. Slow flows with low Reynolds numbers (<100) were considered. RTD measurements were carried out with a step input and the outlet concentration was tracked by measuring light absorbance using a spectrophotometer. The applicability of the axial dispersion model was examined and verified for the studied systems. The axial dispersion was quantified in terms of dispersion coefficients. A significant reduction in the axial dispersion was observed by virtue of multiphase operation, in the order single > gas-liquid > liquid-liquid > gas-liquid-liquid flow. This characterization of backmixing for multiphase flows in curved geometries will be helpful in the optimization of slow reactions in flow and also for processes like nanoparticle synthesis, crystallization, etc.